Petrography and Geochemistry of the Upper Jurassic Siliciclastic Rocks Equivalent to the Mozduran Gas Reservoir in the Eastern Kopet-Dagh Basin, NE Iran - H. Zand-Moghadam; M. Jafarzadeh; R. Moussavi-Harami; A. Mahboubi (Journal of Sciences, Islamic Republic of Iran)
In this research, petrographic and geochemical (major and trace elements) characteristics of siliciclastic rocks of the Mozduran Formation in the eastern Kopet-Dagh Basin have been carried out in order to reveal their provenance such as source area paleoweathering, parent rock composition and tectonic setting. Mozduran Formation is mainly composed of limestone and dolomite, with minor amounts of siliciclastic rocks and evaporites. Siliciclastics rocks (sandstone and shale) of Mozduran Formation are mainly present in the easternmost parts of the Kopet-Dagh Basin. Four stratigraphic sections of Mozduran Formation, namely Kole-Malekabad, Kale-Karab, Deraz-Ab and Karizak, were measured and sampled in the SE of the basin. Petrographic investigation showed that the sandstones are mostly classifies as litharenite and feldspathic litharenite. Geochemical data revealed that CIA values of Mozduran siliciclastic rocks confirm a medium weathering that can be due to semi-arid climatic condition in the source area. Felsic composition of parent rocks and quatzolithic petrofacies of Mozduran Formation sandstones and their constituents such as Qp, Qm, Ls, Lm and F, together with paleocurrent analysis show that these siliciclastic sediments may have derived from uplifted and trusted belt of sedimentary or sedimentary- metamorphic rocks of south Mashhad and metamorphic rocks of north Fariman region. Petrographic and geochemical analyses suggest that these sediments deposited in a continental rifting system.